Effect of clofazimine on nerve function impairment in pauci-bacillary leprosy patients - Poulkar, Chandrakant B.; Chaudhari, Nitin D.; Khatu, Swapna S. (International Journal of Research in Dermatology, 2019)
Background: Clofazimine is a riminophenazine derivative which is useful both for treating the leprosy and managing reactive episodes. Previous studies demonstrated that clofazimine may have a useful prophylactic role against neuritis/type 1 reaction and nerve damage. The WHO Technical Advisory Group (TAG), in its Third meeting in 2002, proposed that uniform MDT regimen (U-MDT) of 6 months duration should be considered to treat all types of leprosy. This study was aimed to determine any additional beneficial effects of clofazimine as part of UMDT in the prevention of nerve function impairment (NFI) in paucibacillary (PB) leprosy patients. Methods: Sixty paucibacillary leprosy patients were randomized into two groups, A and B consisting of 30 patients each. Group A received U-MDT for 6 months and group B received MDT-PB for 6 months. Nerve function assessment (NFA) using various modalities was done at the beginning (0 month) and at the completion of MDT (6 months) and results were compared. Results: No statistically significant difference in improvement or deterioration of NFI was found in two groups. Conclusions: On the basis of present study, we found that addition of clofazimine in standard dose as part of U-MDT has no beneficial role in prevention or improvement of NFI in PB leprosy patients. However, a larger longitudinal study taking substantial number of population in both groups might be helpful to derive any conclusion.